1995
DOI: 10.1182/blood.v85.2.456.bloodjournal852456
|View full text |Cite
|
Sign up to set email alerts
|

Model of Epstein-Barr virus infection of human thymocytes: expression of viral genome and impact on cellular receptor expression in the T- lymphoblastic cell line, HPB-ALL

Abstract: Infection of B lymphocytes and epithelial tissue by Epstein-Barr virus (EBV) is associated with malignancy and autoimmunity. The cellular receptor for EBV has been identified as CD21 (CR2). A molecule, which is biochemically and immunologically similar to B-cell CD21, has been identified on a subpopulation of immature thymocytes, suggesting a role for this molecule in the regulation of T-cell development and further suggesting that immature T cells might be susceptible to EBV infection. A growing body of liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…22 Increasing evidence implies that EBV induces malignant transformation of T-cells, which contributes to the occurrence of EBV-associated HLH and CAEBV. 10 Additionally, Paterson et al 23 was the first to conduct in vitro experiments on EBV infection in T-ALL patients and Sakajiri et al 24 suggested that EBV plays a role in the etiology of T-ALL. We found that EBV infection in B-ALLs (44.9%) was higher than in T-ALLs (8.3%).…”
Section: Discussionmentioning
confidence: 99%
“…22 Increasing evidence implies that EBV induces malignant transformation of T-cells, which contributes to the occurrence of EBV-associated HLH and CAEBV. 10 Additionally, Paterson et al 23 was the first to conduct in vitro experiments on EBV infection in T-ALL patients and Sakajiri et al 24 suggested that EBV plays a role in the etiology of T-ALL. We found that EBV infection in B-ALLs (44.9%) was higher than in T-ALLs (8.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological analysis of the brain lesion in patient 2 revealed that the major infiltration was composed of EBV-infected activated CD4 + T-cells (data not shown). Paterson et al [34,35] indicated that human immature thymocyte was activated after EBV infection and its consequences at an early stage of differentiation might lead to failure of normal T-cell repertoire development. Taken together, the clonal expansion of EBVinfected T-cells may affect the derangement of T-cell diversity and contribute to lymphoproliferation in CAEBV patients.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism by which the T or NK cells are infected by EBV has also not been thoroughly investigated. Here we offered 3 speculations on how TNFRSF13B mutations predispose T and/or NK cells to EBV infection according to previous studies: the TACI protein involves in the EBV binding process (similar to the molecule CD21) 21 ; impaired TACI expression or TACI variants influence the susceptibility of myeloid lineage progenitors to EBV infection 22 ; TNFRSF13B mutations impair the activity of T and/or NK cells in controlling EBV replication at the secondary lymphoid organs, resulting in the high load of virus and subsequent infection. 23 However, considering of the little expression of TACI on CD16 dim NK cells and CTLs (Supplementary Figure 2, http://links.lww.com/BS/A83 ), their vital role in preventing the EBV infection and eliminating the EBV-infected B cells, and the significantly higher expression of TACI on EBV-transformed B cells compared with the normal B cells (data not shown), this work puts forward the hypothesis that TACI may implicate in the T/NK cell–mediated responses against EBV via the ligand–receptor interactions in EBV-infected B cells.…”
Section: Discussionmentioning
confidence: 99%